An Analysis of Factors Influencing Hypertension Occurrence - Maharani, Shintya Devina; Tunjungsari, Feny; Sudarmaji; Triastuti, Nunung; Pratama, Proboyudha (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2023)
The number of hypertension sufferers is expected to continue to increase to reach 1.5 billion individuals in 2025, with deaths reaching 9.4 million individuals. Basic Health Research (Riskesdas) 2013 resulted in the prevalence of hypertension in people aged ≥ 18 years in Indonesia reaching 25.8%, of those diagnosed by health workers and/or having a history of taking medication was only 9.5%, indicating that the majority of hypertension cases in the community have not yet been diagnosed. diagnosed and reached by the health care team. Factor risk hypertension increase on population rural And urban . Factor risk This including smoking , consuming alcohol , and style life that doesn't Lots move . Therapy line First For hypertension is modification style life that consists from decline heavy body , reduction sodium And supplementation potassium , pattern Eat healthy , activity physical and _ restrictions consumption alcohol.  A search was conducted via PubMed, Cochrane, Web of Science, and Google Scholar using the keywords varicella risk factors. 30 journals published at least 5 years ago were obtained. The journal contains topics on various risk factors for varicella. Criteria for accredited national journals and international journals accredited by Scopus and non-Scopus. From 30 articles reviewed there are 2 types factors that become reason happening hypertension . Factors that can changed including diseases _ comorbid , style life , nutritional status , and level worry or depression . Whereas factors that don't can changed including types _ sex And age. From the literature review articles obtained, there are 7 risk factors that cause hypertension, including diseases comorbid , style life , nutritional status , and level worry or depression , type gender , and age .